2009
DOI: 10.1007/s00424-009-0759-7
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-derived contracting factors mediate the Ang II-induced endothelial dysfunction in the rat aorta: preventive effect of red wine polyphenols

Abstract: Angiotensin II (Ang II)-induced hypertension is associated with vascular oxidative stress and an endothelial dysfunction. This study examined the role of reactive oxygen species (ROS) and endothelium-derived contracting factors in Ang II-induced endothelial dysfunction and whether these effects are prevented by red wine polyphenols (RWPs), a rich source of natural antioxidants. Rats were infused with Ang II for 14 days. RWPs were administered in the drinking water 1 week before and during the Ang II infusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 37 publications
3
23
1
3
Order By: Relevance
“…The latter shift in membrane potential was, at least partly, induced by reduced basal NO bio-availability in the vessel wall. Endothelial dysfunction is a common feature in AHT [23], leading to impaired NO synthesis and/or bioavailability [3,13,35,36,42]. We did, however, not find evidence for attenuated NO release evoked by acetylcholine or sensitivity of the VSMCs for exogenous NO.…”
Section: Discussioncontrasting
confidence: 75%
“…The latter shift in membrane potential was, at least partly, induced by reduced basal NO bio-availability in the vessel wall. Endothelial dysfunction is a common feature in AHT [23], leading to impaired NO synthesis and/or bioavailability [3,13,35,36,42]. We did, however, not find evidence for attenuated NO release evoked by acetylcholine or sensitivity of the VSMCs for exogenous NO.…”
Section: Discussioncontrasting
confidence: 75%
“…Although the reduction in COX-derived metabolites caused by Provinols may suggest a reduction in COX activity, further studies are warranted to ascertain the effects of Provinols on COX enzymes' activity. Consistent with our findings, a previous study from Kane et al [40] showed that red wine polyphenols reduced angiotensin II-induced COX-2 overexpression in rat vessels. Previous publications have also reported an inhibitory effect of red wine extract and tea polyphenols on COX-2 activity [20, 38].…”
Section: Discussionsupporting
confidence: 94%
“…with antioxidant properties is actually a real asset in the prevention of chronic diseases, while the importance of prevention should not be underestimated. All publications by Dal et al demonstrated the interest of the use of natural antioxidants (red wine polyphenols) to prevent and treat diseases with endothelial dysfunction related to oxidative stress [62,64,213,471,472]. Moreover, our recent works carried out on in vitro and in vivo models of metabolic disorders have allowed us not only to involve oxidative stress in the pathophysiology of disorders but also to demonstrate that natural antioxidant compounds help to prevent or reduce complications (polyphenols from green tea and red wine [442,473], red cabbage, Dal S, under publication).…”
Section: Discussion and General Conclusionmentioning
confidence: 99%